2004
DOI: 10.1038/sj.jea.7500373
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and cotinine in adults’ urine: The German Environmental Survey 1998

Abstract: In 1998, the German Environmental Survey (GerES III) recruited approximately 5000 adults between the ages of 18 and 69 years. The study population for these analyses consisted of 1580 smokers (34% of the total population) and 3126 nonsmokers. Nicotine and cotinine concentrations in urine were determined by HPLC methods with UV-detection and corrected for creatinine. Nicotine and cotinine concentrations differed between smokers and nonsmokers by factors of 10-100. The multiple linear regression models used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 16 publications
6
36
0
Order By: Relevance
“…Previous reports suggest a linear relationship between cotinine and CPD under 20 to 25 CPD (4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). At higher CPD, the relationship has been observed to increase without diminution (19,23,25,26), increase but at a diminished rate (17, 19-21, 24, 27), or increase to a plateau and possibly even decline (4,16,19,22).…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports suggest a linear relationship between cotinine and CPD under 20 to 25 CPD (4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). At higher CPD, the relationship has been observed to increase without diminution (19,23,25,26), increase but at a diminished rate (17, 19-21, 24, 27), or increase to a plateau and possibly even decline (4,16,19,22).…”
Section: Discussionmentioning
confidence: 91%
“…Data of the German Environmental Survey 1998 indicated that approximately 20% of all adult non-smokers were exposed to ETS at home, in the work place or in other places, when ETS exposure was defined as cotinine excretion in urine (Heinrich et al, 2005). On the basis of the questionnaire data obtained within the German Health Survey 1998, 55% of all adult non-smokers were frequently exposed to ETS.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic exposure to cigarette smoke is commonly monitored by measuring nicotine and its major metabolite cotinine in urine, saliva, blood, and hair (4)(5)(6)(7)(8)(9)(10)(11)(12). In some studies, trans-3 ¶-hydroxycotinine, the major metabolite of cotinine, is used along with nicotine and cotinine to estimate total nicotine uptake and exposure (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%